Metabolic Syndrome, Chronic Kidney, and Cardiovascular Diseases: Role of Adipokines - Manfredi Tesauro; Maria Paola Canale; Giuseppe Rodia; Nicola Di Daniele; Davide Lauro; Angelo Scuteri; Carmine Cardillo (Cardiology Research and Practice)
Obesity is a chronic disease, whose incidence is alarmingly growing. It is associated with metabolic abnormalities and cardiovascular complications. These complications are clustered in the metabolic syndrome (MetS) leading to high cardiovascular morbidity and mortality. Obesity predisposes to diabetic nephropathy, hypertensive nephrosclerosis, and focal and segmental glomerular sclerosis and represents an independent risk factor for the development and progression of chronic kidney disease (CKD). Albuminuria is a major risk factor for cardiovascular diseases (CVDs). Microalbuminuria has been described as early manifestation of MetS-associated kidney damage and diabetic nephropathy. Obesity and MetS affect renal physiology and metabolism through mechanisms which include altered levels of adipokines such as leptin and adiponectin, oxidative stress, and inflammation. Secretory products of adipose tissue also deeply and negatively influence endothelial function. A better understanding of these interactions will help in designing more effective treatments aimed to protect both renal and cardiovascular systems.